2020
DOI: 10.3892/ol.2020.12048
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of SAR1B suppresses proliferation and induces apoptosis of RKO colorectal cancer cells

Abstract: Colorectal cancer (CRC) is the third most commonly diagnosed cancer worldwide. SAR1 gene homolog B (SAR1B) is a GTPase that has been reported to have a central role in the regulation of lipid homeostasis and is associated with numerous diseases. However, its role in cancer, particularly in CRC, remains unclear. The present study revealed that SAR1B was overexpressed in CRC samples and this was associated with shorter overall survival time in patients with CRC. Colony formation, cell proliferation and flow cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
2
2
0
Order By: Relevance
“…After the knockdown of NbSar1 , we found that the proliferation of N. bombycis was significantly inhibited ( Fig. 8 ), which is consistent with previous research showing that the knockdown of Sar1B suppressed cell proliferation and induced significant apoptosis of RKO (colorectal cancer) cells ( 45 ). In Colaphellus bowringi , the knockdown of each gene of COPII considerably inhibited yolk deposition and ovarian growth.…”
Section: Discussionsupporting
confidence: 90%
“…After the knockdown of NbSar1 , we found that the proliferation of N. bombycis was significantly inhibited ( Fig. 8 ), which is consistent with previous research showing that the knockdown of Sar1B suppressed cell proliferation and induced significant apoptosis of RKO (colorectal cancer) cells ( 45 ). In Colaphellus bowringi , the knockdown of each gene of COPII considerably inhibited yolk deposition and ovarian growth.…”
Section: Discussionsupporting
confidence: 90%
“…However, the function of SAR1B in tumors has not been fully explored and was only reported recently to have a correlation with the progression of colorectal cancer. More speci cally, SAR1B knockdown has been shown to hinder the proliferation of colorectal cancer cells in vitro and trigger apoptosis [12,13]. In an agreement, we found that SA1R1B was also essential for in vitro cell proliferation capacity in lung cancer.…”
Section: Sar1b Is Indispensable For In Vivo Tumor Formation Of Lung C...supporting
confidence: 82%
“…Lipid metabolism is an important cellular life process, and abnormalities in its metabolism are also closely related to the development of tumors [11]. Recently, SAR1B is reported to promote proliferation of colorectal cancer cells and induces apoptosis [12], and plays important role in colorectal cancer metastasis [13]. Importantly, Chen et al revealed that SAR1A promoted an mTORC1-dependent growth of lung cancer cells [14].…”
Section: Introductionmentioning
confidence: 99%
“… 16 Recently, it has been reported that some biomarkers are closely related to the prognosis of CRC. High expressions of SAR1B (secretion associated Ras related GTPase 1B), 17 HOXA11‐AS (homeobox A11 antisense RNA), 18 or TRIM24 (tripartite motif containing 24) 19 in CRC samples had the correlation with poor prognosis and shorter overall survival. Meanwhile, low expression of ENO2 and ENO3 were correlated with longer overall survival.…”
Section: Discussionmentioning
confidence: 99%